2017
DOI: 10.1136/sextrans-2016-052938
|View full text |Cite
|
Sign up to set email alerts
|

Screening for asymptomatic neurosyphilis in HIV patients after treatment of early syphilis: an observational study

Abstract: Although the number of patients in our study is modest, single-dose BPG appears to be highly effective even in patients at high risk of neurosyphilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…Currently, despite the lack of consensus on the diagnostic criteria for ANS [7], most studies agree on the generic definition of a pathology characterized by a CSF finding compatible with a neurosyphilis diagnosis in the absence of neurological signs or symptoms. For these reasons, although the definition of ANS remains difficult to clarify and its epidemiological impact has been poorly studied, the most recent guidelines on syphilis definitively recognize this nosological entity [7,8,13]. Actually, in PLWH without neurological signs but with a significant suspicious of ANS due to low levels of CD4 (≤350 cells/mm 3 ) and/or VDRL/RPR title > 1:32, serological failure after previous adequate antibiotic treatment or the use of alternative drugs, the diagnosis of ANS is based principally on CSF abnormalities [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, despite the lack of consensus on the diagnostic criteria for ANS [7], most studies agree on the generic definition of a pathology characterized by a CSF finding compatible with a neurosyphilis diagnosis in the absence of neurological signs or symptoms. For these reasons, although the definition of ANS remains difficult to clarify and its epidemiological impact has been poorly studied, the most recent guidelines on syphilis definitively recognize this nosological entity [7,8,13]. Actually, in PLWH without neurological signs but with a significant suspicious of ANS due to low levels of CD4 (≤350 cells/mm 3 ) and/or VDRL/RPR title > 1:32, serological failure after previous adequate antibiotic treatment or the use of alternative drugs, the diagnosis of ANS is based principally on CSF abnormalities [13].…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic neurosyphilis was defined and diagnosed by a reactive CSF RPR test (or CSF white blood cells >20/μL plus a reactive CSF TP particle agglutination ≥ 1:640.) [7,8] in PLWH asymptomatic for neurological signs or symptoms. Late syphilis was defined as syphilis acquired >2 years previously according with the World Health Organization (WHO) and European Guidelines for syphilis [7].…”
Section: Methodsmentioning
confidence: 99%
“…Given ongoing uncertainties about the significance of asymptomatic neurosyphilis, there remains debate about the need for CSF analysis to assess for neurosyphilis in all asymptomatic patients who were HIV-positive. A recent UK study found that among patients who have received treatment for early syphilis with benzathine penicillin G, the rates of asymptomatic neurosyphilis after treatment are low 29. In view of this the optimal timing and use of lumbar puncture in the management of syphilis remains uncertain 30…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with doxycycline (2 × 200 mg per day [200 mg every 12 h] for 28 days) can be considered as an alternative. The rationale for this treatment approach is the well-known effectiveness (and recommendation) of doxycycline therapy for systemic forms of syphilis [3,38], sufficient penetration of doxycycline into the CSF at a dose of 2 × 200 mg per day [42], and several case reports of positive treatment results with doxycycline in neurosyphilis [42][43][44]. Owing to the lack of randomized studies, however, there is no recommendation from the CDC or the European guideline for the treatment of neurosyphilis with doxycycline [3,25].…”
Section: Antibiotic Therapy Backgroundmentioning
confidence: 99%